Synthesis of CoFe2O4/Graphene Oxide-Grafted Tetraethylenepentamine for Removal of Cr (VI) from Aqueous Solution - Hui Pan; Donglin Zhao; Li Wang (Advances in Condensed Matter Physics)
In this study, amino-functionalized magnetic graphene-based composite TEPA-GO/CoFe2O4 (TGOM) was prepared by a simple one-step hydrothermal reaction and applied to the removal of Cr (VI) from wastewater. The removal of Cr (VI) by TGOM has the characteristics of high removal efficiency and excellent cycle performance. The maximum adsorption capacity is 114.81 mg/g, and the adsorption efficiency can still reach 62% after four cycles. The mass percentage of amino in TGOM material is about 1.97% according to thermogravimetric analysis. The modification by TEPA increased the adsorption sites and improved the adsorption capacities due to the synergistic effect of chelation with Cr (VI). The effects of pH, contact time, and temperature on the removal of Cr (VI) were studied. The removal process accorded with the pseudo-second-order kinetics and Langmuir isotherm model, and the thermodynamic parameters showed that the adsorption process was exothermic and spontaneous. The characterization analysis before and after adsorption showed that there were complexation reaction, electrostatic adsorption, and reduction mechanism in the removal process. The above results indicate that TGOM is an effective adsorption material for the removal of Cr (VI) in wastewater.